2022
DOI: 10.1038/s41467-022-29111-z
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of additivity, dominance, and epistasis on fitness in a diploid yeast cross

Abstract: In diploid species, genetic loci can show additive, dominance, and epistatic effects. To characterize the contributions of these different types of genetic effects to heritable traits, we use a double barcoding system to generate and phenotype a panel of ~200,000 diploid yeast strains that can be partitioned into hundreds of interrelated families. This experiment enables the detection of thousands of epistatic loci, many whose effects vary across families. Here, we show traits are largely specified by a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…However, the additive component was always the largest component of total heritability. The contribution of non-additive or dominance factors to total heritability is consistent with many prior studies, as is the smaller contribution relative to additive effects 12,[15][16][17][18] . However, it remains possible that a portion of the additive effects are in fact due to their underlying effect in interactions 19,20 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the additive component was always the largest component of total heritability. The contribution of non-additive or dominance factors to total heritability is consistent with many prior studies, as is the smaller contribution relative to additive effects 12,[15][16][17][18] . However, it remains possible that a portion of the additive effects are in fact due to their underlying effect in interactions 19,20 .…”
Section: Discussionsupporting
confidence: 87%
“…Integration of this omnigenic model may lead to more accurate genetic models for complex traits, for which current models fail to accurately account for most heritability and similarly fail to accurately predict trait outcomes based on polygenic risk scored in distinct and diverse populations [15][16][17][29][30][31] . These studies were made possible by performing sex-stratified analyses, instead of adjusting for sex as is typically done in most GWAS models.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated here that understanding the prevalence, causes and consequences of genetic dominance not only clarifies the genetic architecture of complex traits [47,51,81] but also improves the power to detect associations. Our work complements earlier studies that have improved genomic prediction in theoretical simulation studies [82,83] and in practical breeding applications for animals [84,85] and plants [86,87].…”
Section: Discussionmentioning
confidence: 87%
“…In future experiments, we aim to model features that have strong main effects and are also involved in epistatic interactions with other loci. It has been observed that loci with strong main effects are also epistatic hubs, involved in many 2- and 3-way epistatic interactions in the genome [ 3 ]. We hope to discover these epistatic hubs as well as epistatic loci without large main effects in future experiments using AutoQTL.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large-scale study in Saccharomyces cerevisiae identified that of the 61% broad-sense heritability detected, 21% was due to non-additive effects (dominance deviations and epistasis) [ 3 ]. In a related previous study, also in S. cerevisiae , of the 91.7% of the phenotypic variance attributed to genetic sources, non-additive effects accounted for 18.7% [ 4 ] Furthermore, non-additive QTL outnumbered additive QTL 3:1.…”
Section: Introductionmentioning
confidence: 99%